2011
DOI: 10.5606/kbbihtisas.2011.040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the duration of postoperative pain control obtained with bupivacaine injection into the tonsillar region in children who underwent tonsillectomy

Abstract: Intraoperative preincisional bupivacain injection is useful in postoperative pain control at early period of time in children undergoing tonsillectomy. But it has no effect in pain reduction after 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
2
Order By: Relevance
“…Ivan et al found that bupivacaine caused significant pain relief at 2 and 6 hours after surgery compared to the control group, but no differences were shown at 24 hours after surgery (9). In our research, however, the pain difference between the two groups continued 24 hours after surgery.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Ivan et al found that bupivacaine caused significant pain relief at 2 and 6 hours after surgery compared to the control group, but no differences were shown at 24 hours after surgery (9). In our research, however, the pain difference between the two groups continued 24 hours after surgery.…”
Section: Discussioncontrasting
confidence: 69%
“…In this measure, the pain was measured using a visual analogue pain scale, where 0 represents no pain, and 10 represents unbearable pain. The amount of nausea and vomiting experienced by the patients was evaluated utilizing the post-operation nausea and vomiting scale; a PONV of 0 indicates no nausea or vomiting, 1 nausea but no vomiting, 2 vomited once in 30 minutes, and 3 as two or more episodes in 30 minutes (9). Patients were discharged in the afternoon if the surgery was performed in the morning, and patients were discharged the next day if the surgery was performed in the evening.…”
Section: Study Settings and Interventionsmentioning
confidence: 99%
“…Findings revealed that 0.5% bupivacaine could significantly lower patients' pain in different time after tonsillectomy comparing with the control group (p<0.05). In a similar study by Ihvan et al, bupivacaine was effective in controlling pain several hours after the operation, but 24 hours later, it was not as much effective (14). In our research though, the pain difference between two groups continued by 24 hours after the operation.…”
Section: Discussioncontrasting
confidence: 51%
“…As the preventive method of reducing postoperative pains by blocking the pain impulses and preventing from their entrance into the central nerve systems, bupivacaine infiltration produces analgesia(12). Some studies in some countries have reported the significant effect of this drug on relieving post-tonsillectomy pain (13)(14)(15)(16). Some others though do not consider it as an effective way to prevent from pain (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Ihvan et al . in their study demonstrated that pre‐incisional bupivacaine infiltration significantly reduced postoperative pain scores at postoperative 2nd and 6th hours, but no difference was found between study and control groups at 24th h postoperative and first week.…”
Section: Discussionmentioning
confidence: 91%